A Hybrid Technique for Searching a Reusable Component from Software Libraries - Bhatia, Rajesh K.; Dave, Mayank; Joshi, R.C (DESIDOC Journal of Library & Information Technology, 2010)
Reusing a previously developed and tested software component is the key to improve the quality and productivity of the software. Searching a software from a software library with an intent to reuse it is similar to searching a book from a library. Locating a book or document in library may not be that difficult as searching a reusable component in a software library. The main challenge in reusing software component lies in the retrieval and selection of the appropriate component that would need no or least adaptation from a software component library. Book can be searched on title, authors or some keywords, but these features are not sufficient for searching the required functionality in a component library. Using formal specifications to represent software components facilitates the determination of reusability of the software component. The functionality of the software, and the welldefined syntax of formal language makes processing amenable to automation. In this paper, a hybrid model based on natural language and formal specifications using K-nn technique has been discussed. Benefits of both formal methods and natural language have been exploited for the retrieval of reusable software components. Existing components have been weighted according to their degree of similarity on the basis of certain attributes to the required component. http://dx.doi.org/10.14429/djlit.27.5.137